Microbial derived antimicrobial peptides as potential therapeutics in atopic dermatitis - Joshi, Aaroh Anand; Vocanson, Marc; Nicolas, Jean-Francois; Wolf, Peter; Patra, Vijaykumar (Frontiers in Immunology, 2023)
Atopic dermatitis (AD) is a common chronic inflammatory skin disease that significantly affects the patient’s quality of life. A disrupted skin barrier, type 2 cytokine-dominated inflammation, and microbial dysbiosis with increased Staphylococcus aureus colonization are critical components of AD pathogenesis. Patients with AD exhibit decreased expression of antimicrobial peptides (AMPs) which is linked to increased colonization by Staphylococcus aureus. The skin microbiome itself is a source of several AMPs. These host- and microbiome-derived AMPs define the microbial landscape of the skin based on their differential antimicrobial activity against a range of skin microbes or their quorum sensing inhibitory properties. These are particularly important in preventing and limiting dysbiotic colonization with Staphylococcus aureus. In addition, AMPs are critical for immune homeostasis. In this article, we share our perspectives about the implications of microbial derived AMPs in AD patients and their potential effects on overlapping factors involved in AD. We argue and discuss the potential of bacterial AMPs as therapeutics in AD.